Analisis Pengaruh Profitabilitas dan Solvabilitas terhadap Audit Report Lag dengan Financial Distress sebagai Variabel Intervening pada Perusahaan Sektor Basic Industry and Chemicals yang Terdaftar di Bursa Efek Indonesia - B2092182005, Julianti (MAKSI UNTAN, 2020)
Analisis Pengaruh Profitabilitas dan Solvabilitas terhadap Audit Report Lag dengan Financial Distress sebagai Variabel Intervening pada Perusahaan Sektor Basic Industry and Chemicals yang Terdaftar di Bursa Efek Indonesia Julianti1Program Studi Magister Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tanjungpura ABSTRACT This study aims to analyze the influence of profitability and solvency on audit report lag with financial distress as the intervening variable in basic industry and chemicals companies that listed on Indonesia Stock Exchange. The research method used in this study is the quantitative method. The statistic method used in this study is path analysis. The data sampling method of this study is purposive sampling. The study sample includes 42 basic industries and chemicals companies listed on Indonesia Stock Exchange from 2016 until 2018. The findings show that profitability has no influence on financial distress but has influence on audit report lag and has the indirect influence on audit report lag with financial distress as the intervening variable. Solvency has influence on financial distress and audit report lag and also has the indirect influence on audit report lag with financial distress as the intervening variable. Financial distress has influence on audit report lag.Keywords: Profitability, Solvency, Financial Distress, Audit Report Lag (ARL).